Bangladesh Climate Change Adaptation Survey (BCCAS), Round II - International Food Policy Research Institute; Data Analysis and Technical Assistance; University of Bonn (International Food Policy Research Institute, 2014)
The Bangladesh Climate Change Adaptation Survey (BCCAS), Round II is a follow up survey to BCCAS, Round I. About 97.34 percent of households from BCCAS I were reinterviewed in 2012. The survey captures information on demographic characteristics, social capital, land tenure, crop and livestock management, input use, extension, incidence of climatic shocks in the last five years and adaptation options and if there are any changes from 2010 survey. . The survey was conducted from September to October 2012, covering data from the previous production year. It covers households in the 7 broad agroecological zones as grouped by the Bangladesh Center for Advanced Studies. (2014-11-21)